The Role of Proactive Personality, Work-Related Flow, and Job Satisfaction in Promoting Employee Innovative Behavior - Mely Wahyuningsih; Lista Meria (Jurnal Ilmiah Manajemen dan Bisnis, 2026)
Innovation is essential for organizational growth, with employee innovative behavior playing a pivotal role in driving innovation. This study examines the influence of proactive personality, job satisfaction, and work-related flow on enhancing employee innovative behavior. Using a quantitative approach with Structural Equation Modeling-Partial Least Squares (SEM-PLS) and SmartPLS 4.1, data were collected from 210 employees in the information technology industry in West Jakarta through purposive sampling. The results indicate that proactive personality positively affects employee innovative behavior and work-related flow, while work-related flow positively influences employee innovative behavior and mediates the relationship between proactive personality and employee innovative behavior. Additionally, job satisfaction significantly enhances employee innovative behavior. These findings provide valuable insights for organizations to develop strategies that foster employee innovative behavior effectively.